What has made deer farming in New Zealand so successful? The importance of venison quality, understanding the industry, the market and the biology of the animals - Pearse, A. J. (Rangifer, 1990)
In summarising these aspects of success within the NZ deer industry we can note: (1) NZ traditional farming skills of pasture based production have been readily adapted to deer farming. (2) The industry has grown with strength through the diversity of its participants, leading farmers, innovative researchers, business investors and leaders and the NZDFA and its membership. All are united in their determination that market signals, rather than farm production demands should shape the development of venison supply and presentation. (3) The frank and rapid exchange of research results, farmer innovation, market information and exchange of experience and ideas within the industry. (4) The overwhelming commitment to quality production. Biologically, deer has their own contributing attributes: (a) they are intelligent and easy to farm; (b) they are efficient converters of pasture and supplements to venison or to progeny; (c) they thrive throughout NZ varied agricultural terrain on native grasses or improved pasture, and have a healthy and long productive life; (d) they have enormous climatic and environmental tolerance, a defined breeding season and predictable calving pattern; (e) they are immensely seasonal, and now, when feeding and breeding requirements are well understood in terms of that seasonality, productive growth targets are readily set and achieved to accommodate the market signal; (f) they are simple to manage with a minimum of labour and physical inputs.